Dual Nitrate Stable Isotopes of SONNE 305 cruise in the East Equatorial Indian Ocean and Bay of Bengal - Gesa Schulz; Jan Penopp (PANGAEA, 2025)
This dataset includes dual nitrate stable isotope collected at 21 stations of the R/V Sonne cruise SO305 BIOCAT-IIOE2 (10 April – 22 May 2024). Samples were collected at 21 stations at selected water depths from Niskin Bottles attached to the CTD. Dual nitrate stable isotopes were measured during the denitrifier method. This data was used to study nitrogen cycling in the Bay of Bengal and East Equatorial Indian Ocean.